The keepers of the flame - Armstrong, Jennifer, 1961- (Armstrong, Jennifer, 1961- Fire-us trilogy, 2002)
After a virus destroys most of the world's adult population, a group of children are delighted to discover a colony of adult survivors in a Florida shopping mall but soon find that they are not as friendly as they appear.